Exploring online prices with an advance booking horizon on Booking.com - Sánchez-Lozano, Gloria (2020)
The online market enables hotels to enhance their visibility and drive up their revenue. This study analysed both the average room price and price count (i.e. the sum of the number of prices that hotels offer) on Booking.com for a period of 300 days prior to check-in, with data classified by official hotel category. Hotels’ number of rooms, day of the week, room type, room capacity (i.e. maximum number of guests per room) and length of stay were also tracked. This research was based on a stratified sample of hotels gathered by using random sampling and proportional allocation, as well as defining the strata by hotel categories. The dataset included 1,353,751 records. The results reveal that channel management activities are an important area of hotels’ operations, which generate a considerable workload in terms of the time devoted to updating data and other related tasks. However, hotels’ participation in online channels does not always match their importance in the market as measured by their relative numberof rooms. Most of the variables under study have a significantpositiveimpact on prices, except for hotels’ number of rooms, which failed to follow any discernible pattern of influence.